Implementasi Metode Ward & Peppard dalam Perancangan Blueprint Smart Village Sudagaran - Kusumawardani, Dwi Mustika; Wiguna, Citra; Rakhmadni, Diovianto Putra; Br. Karo, Ella Manisa (Jurnal Sistem Informasi Bisnis, 2024)
According to Village Law No. 6 of 2014, villages play an important role in the implementation of village development policies. The government-mandated village regulations must be followed in order to improve the quality of life in rural communities. This can be accomplished through the enhancement of services and the development of sustainable villages. The smart village concept is one of the strategic steps for improving village development. Smart village indicators are adapted from smart cities, one of which is smart government, to map village development. Smart government can increase community members' empowerment and involvement in public management, as well as transparency in decision-making and the maintenance of governance that emphasizes the capacity of village officials, village institutions, and the delivery of basic services. To begin the process of creating a smart village, a blueprint must be created. The Ward and Peppard method can be used to create the design. The Ward and Peppard method is used in this study, and it begins with a mapping diagram that includes value chain analysis, SWOT, key performance indicators, McFarlan, and PEST. The design of the village development strategy is carried out by analyzing the organization's internal and external conditions, including business processes and IS/IT infrastructure. The research results in a smart village blueprint design document, which is expected to be implemented to realize the village in building village social resilience in a sustainable manner, as well as providing basic government services in a precise and transparent way.